2016
DOI: 10.1590/1806-9282.62.09.853
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for choosing the profession and profile of newly qualified physicians in Brazil

Abstract: Reasons foR choosing the pRofession and pRofile of newly qualified physicians in BRazil rev assoc Med Bras 2016; 62(9):853-861 853 ORIGINAL ARTICLEReasons for choosing the profession and profile of newly qualified physicians in Brazil Objective: To evaluate the socio-demographic profile, path to medical school admission and factors affecting the choice of becoming a physician in Brazil.Method: Application of a structured questionnaire to 4,601 participants among the 16,323 physicians who graduated between 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 17 publications
1
17
0
7
Order By: Relevance
“…In the present study, physician was the profession most reported, and the vast majority of professionals were women, in agreement with past research that has observed increased numbers of women in medical schools and residency programs around the world (21,22). The result of the present study was different from that of research on MD/PhD programs in Canada and the United States, which found that men were the predominant gender (9,10,13,20).…”
Section: ' Discussionsupporting
confidence: 77%
“…In the present study, physician was the profession most reported, and the vast majority of professionals were women, in agreement with past research that has observed increased numbers of women in medical schools and residency programs around the world (21,22). The result of the present study was different from that of research on MD/PhD programs in Canada and the United States, which found that men were the predominant gender (9,10,13,20).…”
Section: ' Discussionsupporting
confidence: 77%
“… 18 , 21 Indeed, this finding is related to the increase of women in medical schools and residency programs around the world. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…We adapted Bland, Meurer, and Maldonado's 1995 model of the determinants of students' choices of specialties [11] and divided potential influencing factors into the following: (a) student's personal and socio-economic characteristics (gender, family income, age); (b) type of school attended (secondary school, medical school of training, urban or rural location of the schools); (c) student's needs to satisfy personal and societal expectations (intrinsic and extrinsic motivation); (d) perception of specialty characteristics (prestige, working hours, contact with patients, social role and prospective earnings. We identified suitable variables from the 'Profile and perceptions of new graduates in medicine in Brazil' survey study [29] as proxies for the above factors.…”
Section: The Methodological Approachmentioning
confidence: 99%
“…We used secondary data from a representative crosssectional survey conducted in 2015 by the São Paulo University [29], to perform descriptive, multivariate logistic, and multilevel analysis on the effect of a range of variables on students' declared intention to practice in primary care settings. The survey dataset had 4601 respondents from a population of 16 323 eligible newly graduated physicians.…”
Section: Data Set and Variablesmentioning
confidence: 99%